2015
DOI: 10.1007/s10865-015-9696-4
|View full text |Cite
|
Sign up to set email alerts
|

Affect, work-goal schemas, and work-goal striving among adults with chronic pain: a multilevel structural equation analysis

Abstract: For individuals with chronic pain, the within-person influence of affect and goal cognition on daily work-related goal striving is not yet well understood. The present study tested the hypothesis that anticipatory goal cognition in the form of a morning work goal schema mediates the relations between morning affect and later (afternoon and evening) work goal striving. Working adults with chronic pain (N = 131) completed a 21-day diary with morning, afternoon, and evening assessments analyzed via multi-level st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…These results are in line with findings from another study showing a positive association between positive and negative affect and goal representations. These representations facilitate goal pursuit and are related to depression levels (Karoly & Ruehlman, ; Mun, Karoly, Okun, Kim, & Tennen, ). This study represents a first step that opens up the possibility of carrying out research to test whether positive affect is a causal and significant buffer between pain and pain‐related outcomes (Reme, ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with findings from another study showing a positive association between positive and negative affect and goal representations. These representations facilitate goal pursuit and are related to depression levels (Karoly & Ruehlman, ; Mun, Karoly, Okun, Kim, & Tennen, ). This study represents a first step that opens up the possibility of carrying out research to test whether positive affect is a causal and significant buffer between pain and pain‐related outcomes (Reme, ).…”
Section: Discussionmentioning
confidence: 99%
“…Such fluctuations may reflect situational factors that undermine or facilitate goal planning or effort in daily life. Daily diary studies examining adults with chronic pain have identified personal and situational factors such as daily pain, fatigue, and positive or negative affect that contribute to day-to-day fluctuations in daily goal planning, goal effort, and ultimately goal progress (Affleck et al, 2001; Karoly et al, 2014; Mun, Karoly, Okun, Kim, & Tennen, 2016). Mulvaney and colleagues (2011) identified barriers to T1D management in younger adolescents, but late adolescents may experience unique daily barriers as they manage their T1D increasingly away from home and more independently from parents (Wdowik, Kendall, & Harris, 1997).…”
Section: Discussionmentioning
confidence: 99%